PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA KELAS X SMA NEGERI 2 SUNGAI RAYA - Lestari, Rara (Jurnal Pendidikan Sosiologi dan Humaniora, 2018)
This research aimed to investigate how the effect of make a match model on learning achievement of tenth grade students of SMA Negeri 2 Sungai Raya regency. The method used was quasi experimental that comprised two sample classes as control class and experimental class. The sample were selected using purposive sampling. The result showed that: (1) the mean score of students"™ learning achievement before make a match method applied was 70,36 76 (KKM). It means the mean score of students"™ learning achievement was low, as its excess difference was 5,64 from KKM. The mean score of students"™ learning achievement after using make a match model was 80,85 76 (KKM). It means the mean score of students"™ learning achievement was quite high distinguish from the excess difference of the enhancement of students"™ learning achievement mean score as 4,85 Ëƒ 5,64 (control class learning achievement mean score). (2) there was an effect on students"™ learning achievement in sociology learning on the material"students"™ sosialization" of tenth grade students of SMA Negeri 2 Sungai Raya, between the students who did not apply make a match method and the students who applied make a match methodas t-test Polled Varians obtainedthitung   4,59 and ttabel 0,104 with significant level (Î±) = 5% and dk = 60.   In conclusion, Ha was acceptable and Ho was rejected. (3) the effect of the use of make a match method on students"™ learning achievement of tenth grade students of SMA Negeri 2 Sungai Raya on the material "students"™ sosialization" was 0,92 with high category.